The dissipation of profenofos, λ-cyhalothrin and chlorothalonil in vegetable and soil under humid tropical condition - Henry, Michelle Crystal (Universiti Malaysia Sarawak (UNIMAS), 2015)
The dissipation dynamic of 3 pesticides, namely profenofos, λ-cyhalothrin and chlorothalonil in green mustard and soil was studied. Field experiments were conducted in dry and wet season under net house and open field to determine the dissipation rate, halflife (t1/2) and pre-harvest interval (PHI) of these pesticides in green mustard and soil. The green mustard was treated with commercial profenofos (ELAK 45EC), λ-cyhalothrin (ALERT 2.8EC) and chlorothalonil (Daconil 2787) at recommended dosage following good agricultural practice. Residue of pesticides in green mustard and soil were determined after the second pesticides application over a period of 22 days. Dissipation of all 3 pesticides in green mustard was fitted the pseudo first order kinetic. Calculated half-lives of profenofos, λ-cyhalothrin and chlorothalonil in green mustard during dry and wet season were 0.66‒0.72 day and 1.28‒1.76 days; 1.18‒1.25 days and 2.51‒3.69 days; 0.93‒1.07 days and 2.01‒2.21 days, respectively. In incubated soil, calculated half-life was 24 days, 37 days, and 15.2 days for profenofos, λ-cyhalothrin and chlorothalonil respectively. The 3 pesticides dissipation in both green mustard and soil followed biphasic dissipation pattern, with faster dissipation in phase I (0‒3 days) and manifesting slower rate of dissipation in phase II (3‒22 days). Results obtained from this study showed pesticides’ physicochemical properties, cultivation systems used and climatic factors such as sunlight radiation, surrounding temperature and rainfall influenced the dissipation rate of pesticides. The dissipation rate of pesticides in vegetable and soil under humid tropical climate was found to be faster compare to temperate and subtropical region with lower surrounding temperature. λ-cyhalothrin residue dissipated below tolerance level after 3 days. However, longer pre-harvest interval of 14‒22 days was required for profenofos and chlorothalonil to comply with the national tolerance level of 0.01 mg kg-1. The long waiting period suggested that repeated application of profenofos and chlorothalonil onto green mustard is not recommended 14 days prior to harvest.